Mapping the widespread distribution and transmission dynamics of linezolid resistance in humans, animals, and the environment - Weiyi Shen; Chang Cai; Ning Dong; Jiawei Chen; Rong Zhang; Jiachang Cai (Microbiome, 2024)
Abstract Background The rise of linezolid resistance has been widely observed both in clinical and non-clinical settings. However, there were still data gaps regarding the comprehensive prevalence and interconnections of linezolid resistance genes across various niches. Results We screened for potential linezolid resistance gene reservoirs in the intestines of both humans and animals, in meat samples, as well as in water sources. A total of 796 bacteria strains out of 1538 non-duplicated samples were identified to be positive for at least one linezolid resistance gene, optrA, poxtA, cfr, and cfr(D). The prevalence of optrA reached 100% (95% CI 96.3–100%) in the intestines of pigs, followed by fish, ducks, and chicken at 77.5% (95% CI 67.2–85.3%), 62.0% (95% CI 52.2–70.9%), and 61.0% (95% CI 51.2–70.0%), respectively. The meat and water samples presented prevalences of 80.0% (95% CI 70.6–87.0%) and 38.0% (95% CI 25.9–51.9%), respectively. The unreported prevalence of the cfr(D) gene was also relatively higher at 13.0% (95% CI 7.8–21.0%) and 19.0% (95% CI 10.9–25.6%) for the feces samples of ducks and pigs, respectively. Enterococci were the predominant hosts for all genes, while several non-enterococcal species were also identified. Phylogenetic analysis revealed a significant genetic distance among linezolid resistance gene reservoirs, with polyclonal structures observed in strains within the same niche. Similar genetic arrays harboring assorted insertion sequences or transposons were shared by reservoirs displaying heterogeneous backgrounds, though large diversity in the genetic environment of linezolid resistance genes was also observed. Conclusions The linezolid resistance genes were widespread among various niches. The horizontal transfer played a crucial role in driving the circulation of linezolid resistance reservoirs at the human-animal-environment interfaces. Video Abstract